Epidemiological profile of patients with hepatitis B and C in a municipality of Minas Gerais (Research, Society and Development, 2026)
Viral hepatitis are diseases caused by different viruses, all hepatotropic, classified as A, B, C, D and E. Currently, it is a public health problem in Brazil, with an annual increase in incidence, mainly due to viruses B and C. Objective: To analyze the epidemiological profile of patients with these viruses, in Lavras, Minas Gerais. Method: This is a descriptive, quantitative, documentary analysis research. The information was obtained from secondary notification data from patients at the Special Care Service/Testing and Counseling Center (SAE/CTA). Results: 80 medical records of laboratory-confirmed diagnoses were analyzed, of which 12 were HBV and 68 HCV, 26 women and 54 men, including white, brown and black people, with variable infection mechanisms, with an average age of 44.4 years for hepatitis B and 53.4 years for hepatitis C and only 20 members with a complete vaccination schedule against hepatitis B. Conclusion: Viral hepatitis remains with alarming cases and restrictions on the spread of the virus are necessary, through the implementation of strategic measures, based on the data exposed on sociodemographic, individual and collective characteristics of research participants.